2023
DOI: 10.3390/genes14081611
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Weir Construction in Korea’s Nakdong River on the Population Genetic Variability of the Endangered Fish Species, Rapid Small Gudgeon (Microphysogobio rapidus)

Abstract: Microphysogobio rapidus, an endemic cyprinid fish species found exclusively in Korea, has been identified in only two tributaries of the Nakdong River. The species predominantly occupies the near-gravel bottom waters within shallow sections of the middle and lower reaches of the river, characterized by swift currents. M. rapidus is currently recognized as a critically endangered species due to its distinct habitat preference, as well as the negative impacts of stream dam development and water environment pollu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
2
1
Order By: Relevance
“…P. tenuicorpa inhabits the Hangang River water system, which is similar to the habitat of M. longidorsalis. The genetic structure of P. tenuicorpa is divided into the Namhangang and Bukhangang rivers [20]. In contrast, this study showed that the M. longidorsalis population was not divided into Namhangang and Bukhangang River genetic structures due to little genetic difference.…”
Section: Genetic Structure Populationscontrasting
confidence: 62%
See 1 more Smart Citation
“…P. tenuicorpa inhabits the Hangang River water system, which is similar to the habitat of M. longidorsalis. The genetic structure of P. tenuicorpa is divided into the Namhangang and Bukhangang rivers [20]. In contrast, this study showed that the M. longidorsalis population was not divided into Namhangang and Bukhangang River genetic structures due to little genetic difference.…”
Section: Genetic Structure Populationscontrasting
confidence: 62%
“…Microsatellites have been mainly reported in studies on the genetic structure and diversity of the Gobioninae subfamily. Consequently, significant genetic diversity and structures were reported [20][21][22]. Microsatellites are commonly analyzed in population genetics studies because of their high intraspecific polymorphism and codominance [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Inbreeding depression has been linked to population survival and reproduction [ 9 , 31 ]. Inbreeding increases homozygosity and deleterious allele frequencies, ultimately leading to a loss of genetic diversity [ 32 ].…”
Section: Discussionmentioning
confidence: 99%